Solid‐State Prelithiation Enables High‐Performance Li‐Al‐H Anode for Solid‐State Batteries - Pang, Yuepeng; Wang, Xitong; Shi, Xinxin; Xu, Fen; Sun, Lixian; Yang, Junhe; Zheng, Shiyou (Advanced energy materials, 2020)
Lithium alanates exhibit high theoretical specific capacities and appropriate lithiation/delithiation potentials, but suffer from poor reversibility, cycling stability, and rate capability due to their sluggish kinetics and extensive side reactions. Herein, a novel and facile solid‐state prelithiation approach is proposed to in situ prepare a Li3AlH6‐Al nanocomposite from a short‐circuited electrochemical reaction between LiAlH4 and Li with the help of fast electron and Li‐ion conductors (C and P63mc LiBH4). This nanocomposite consists of dispersive Al nanograins and an amorphous Li3AlH6 matrix, which enables superior electrochemical performance in solid‐state cells, as much higher specific capacity (2266 mAh g−1), Coulombic efficiency (88%), cycling stability (71% retention in the 100th cycle), and rate capability (1429 mAh g−1 at 1 A g−1) are achieved. In addition, this nanocomposite works well in the solid‐state full cell with LiCoO2 cathode, demonstrating its promising application prospects. Mechanism analysis reveals that the dispersive Al nanograins and amorphous Li3AlH6 matrix can dramatically enhance the lithiation and delithiation kinetics without side reactions, which is mainly responsible for the excellent overall performance. Moreover, this solid‐state prelithiation approach is general and can also be applied to other Li‐poor electrode materials for further modification of their electrochemical behavior. Solid‐state prelithiation of LiAlH4 through a short‐circuited electrochemical reaction leads to a uniform distribution of Al nanograins in an amorphous Li3AlH6 matrix, which enables superior electrochemical performance in solid‐state cells due to the kinetic enhancement. This strategy can also be applied to other Li‐poor electrode materials for further improvement.